Implementation of political party financial assistance policy in political education in Denpasar City - I Nyoman Subanda; Putu Adhismara Kirana (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
Implementing political party financial assistance policies for political education in Denpasar City is regulated by Law No. 2 of 2011 and Ministry of Home Affairs Regulation No. 36 of 2018. This assistance is distributed proportionally ally to political parties that hold seats in the local parliament (DPRD), prioritizing political education. However, its implementation faces several challenges, including the limited role of political parties in effectively conducting political education and the general apathy of young people towards politics. Based on a descriptive qualitative approach, the results indicate that public political participation, particularly in elections, needs to be higher. These findings ings are expected to provide input for improving the effectiveness of policies and increasing political involvement in Denpasar City.